Productivity, Resource Use Efficiency and Cropping Patterns: An Economic Study of Transmigrants in Sumatra, Indonesia - Hendrakusumaatmaja, Sutara (1984)
The objectives of the study were to determine the relationships among factors of production and to examine the influence of status of transmigrant, cropping pattern and farm size on the productivity and efficiency of resource use in transmigrant farms in Sumatra, Indonesia. The Cobb-Douglas production function was fitted to estimate the input-output relationships for 295 transmigrant respondents based on their transmigrant status, cropping pattern and farm size in the Way Abung II Transmigration Project. However, for comparison of results, the Translog model was also fitted. The results of the Translog model was no better than those of the Cobb-Douglas model. Farm production process in the study area exhibit constant returns to scale. Productivity varies with cropping patterns. All inputs, except seed, are used inefficiently on the average farm. Land and material s used on crop maintenance are too low relative to the optimal level because of the lack of capital. The use of labour exceed s the optimum level, because family labour is largely used and surplus family labour is common. The real location of input use would enhance agricultural productivity and result in higher incomes . Efficiency of input us e varies with transmigrant status, farm size and cropping pattern. Returns to labour for farm production activity in the area, except for those farms adopting cropping pattern H (Paddy + Corn + Cassava + Peanuts ), are lower than the wages obtainable from off-farm activity. Transmigrants should be steered into selecting cropping patterns that produce high returns. Cropping pattern H has the highest gross returns/gross margins per hectare but only two per cent of the respondents chose this cropping pattern. The importance of agricultural credits, agricultural extension, and provision of marketing and infrastructural facilities to encourage the choice of such cropping patterns, so as to maximise resource use is evident from this study.